2023
DOI: 10.3390/microorganisms11030585
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Pathogens Associated with Aerial Symptoms of Avocado (Persea americana Mill.) in Tenerife (Canary Islands, Spain) Focused on Species of the Family Botryosphaeriaceae

Abstract: Fungi of the family Botryosphaeriaceae are considered responsible for various symptoms in avocado such as dieback, external necrosis of branches and inflorescences, cankers on branches and trunks, or stem-end rot of fruits. In recent years, these problems are becoming more frequent in avocado orchards in the Canary Islands (Spain). This work includes the characterization of fungal species involved in these diseases, which were isolated from avocado crops in Tenerife Island between 2018 and 2022. A total of 158… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Due to its high lipid and moisture content, low carbohydrate content, and non-acidic pH, previous studies have shown that avocados can be a good growth medium for pathogens ( FDA, 2018 ). Fungal infection, physical harm, lenticel breakdown, water loss, cold injury, or a combination of these causes may all contribute to this disease ( Hernández et al, 2023 ). Previous investigations carried out in different climatic zones in Peru indicate that black spot symptoms and nearby green tissue on the same fruit are likely related to physical damage, fungal invasion, and chilling injury ( Everett et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to its high lipid and moisture content, low carbohydrate content, and non-acidic pH, previous studies have shown that avocados can be a good growth medium for pathogens ( FDA, 2018 ). Fungal infection, physical harm, lenticel breakdown, water loss, cold injury, or a combination of these causes may all contribute to this disease ( Hernández et al, 2023 ). Previous investigations carried out in different climatic zones in Peru indicate that black spot symptoms and nearby green tissue on the same fruit are likely related to physical damage, fungal invasion, and chilling injury ( Everett et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this new scenario, together with the current climate change situation, have favored the increase in almond diseases [2][3][4]. Among them, woody canker diseases, associated with fungi of the Botryosphaeriaceae family, affect a great number of agronomically important woody crops such as olive, grapevine, avocado, blueberry, stone fruit, citrus and nut crops, including almond [5][6][7][8][9][10][11][12]. These diseases affect the trunk and branches of young and mature almond trees causing cankers, extensive gumming, dieback, discoloration and necrosis of internal tissues and, especially in severe cases and young trees, plant death.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, abiotic factors such as physical damage and humidity have been related to lenticel damage [6]. Several investigations have been carried out in different countries to identify pathogens associated with diseases affecting avocado fruit, among which the genera Lasiodiplodia, Neofusicoccum, Fusarium, Penicillium, Aspergillus and Geotrichum have been described [7][8][9]. In Colombia, these problems have gained special attention due to their increased incidence in the field and the rejection of fruit in processing plants, which has generated significant economic losses.…”
Section: Introductionmentioning
confidence: 99%